Selection and optimization of cultivation conditions for bacterial cellulose producer (International Journal of Biology and Chemistry, 2022)
The aim of this study was to increase productivity of Komagataeibacter xylinus C3 strain on nutrient media using industrial wastes as carbon source. By-product of sugar production, molasses, was selected for the cultivation of bacterial cellulose (BC) producer. It has been shown that the significant accumulation of BC (11.9 g/L) occurs on molasses medium with 7 days of cultivation in static conditions, which is 1.6 times higher than on modified Hestrin and Schramm (MHS) medium. BC synthesized on molasses medium is of high mechanical properties (tensile strength – 38.34 MPa and relative elongation at break – 3.34%). The replacement of carbon source for molasses in MHS medium for BC production did not alter the polymer structure and its microfibrillar nature was not affected by the composition of the medium. The introduction of molasses as nutrient source promoted a significant cost decrease of culture media by almost 2.8 times relating to MHS medium cost.